2006
DOI: 10.1002/bit.20877
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the remediation of heavy metal liquid wastes via off-gases produced byKlebsiella pneumoniae M426

Abstract: When the off-gas from an aerobic culture of Klebsiella pneumoniae M426 grown in the absence of added heavy metals was passed through a solution of Hg(2+), Cd(2+), Pb(2+), or Cu(2+) a yellow-white (Hg), white (Cd, Pb), or blue (Cu) precipitate was formed. Metal removal from solution was >97% within 2 h at initial concentrations of (as metal): Hg, 8.5; Cd, 12.6; Pb, 7.8; Cu, 9.5 mg/mL. Mercury was removed from solution at pH 2 and in up to 1 M NaCl. Energy dispersive X-ray microanalysis (EDX) of the precipitates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 47 publications
4
27
0
1
Order By: Relevance
“…Precipitation of HgS by bacteria releasing H 2 S has been proposed as a method for mercury removal (4,(17)(18). Mercury precipitation can also result from the production of volatile organosulfur compounds, yielding precipitates containing mercury together with sulfur and carbon (17). Since the release of dimethyl disulfide has been reported previously for a Serratia marcescens strain (40), a precipitate containing Hg, S, and C can be proposed here for S. marcescens HG19.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Precipitation of HgS by bacteria releasing H 2 S has been proposed as a method for mercury removal (4,(17)(18). Mercury precipitation can also result from the production of volatile organosulfur compounds, yielding precipitates containing mercury together with sulfur and carbon (17). Since the release of dimethyl disulfide has been reported previously for a Serratia marcescens strain (40), a precipitate containing Hg, S, and C can be proposed here for S. marcescens HG19.…”
Section: Discussionmentioning
confidence: 81%
“…Precipitation of mercury with sulfide or organosulfur compounds is a detoxification mechanism described as a mercury tolerance mechanism rather than an effective resistance process (4,21). Precipitation of HgS by bacteria releasing H 2 S has been proposed as a method for mercury removal (4,(17)(18). Mercury precipitation can also result from the production of volatile organosulfur compounds, yielding precipitates containing mercury together with sulfur and carbon (17).…”
Section: Discussionmentioning
confidence: 99%
“…3Cii) was treated with biogas from a culture of K. pneumoniae as described previously (Essa et al 2005(Essa et al , 2006 or, in some experiments, using biogas made in the same way from E. coli. Organothiols from the breakdown of sulphur-amino acids (Essa et al 2005(Essa et al , 2006 together with an alkalinisation of the medium attributable to production of ammonia or volatile amines by the culture (Essa et al 2006) were shown previously to mediate the removal of copper from solution as a mixture of hydroxide and sulphate (Essa et al 2006). Accordingly, copper was precipitated from the Pd-depleted solution as a blue-green precipitate (Fig.…”
Section: Identification Of the Materials Accumulated On The Biomassmentioning
confidence: 99%
“…H 2 was sparged for 30 min and precipitation was followed over 45 min and left to go to completion over 24 h under gravity. The precious metal-depleted solutions were then treated using biogas from broth-grown cultures of Klebsiella pneumoniae or, in some tests, E. coli, as described previously (Essa et al 2005(Essa et al , 2006. Residual metals were analysed commercially as described above.…”
Section: Removal Of Gold and Palladium From Test Solutionsmentioning
confidence: 99%
See 1 more Smart Citation